Expression of malic enzyme reveals subcellular carbon partitioning for storage reserve production in soybeans - Morley, Stewart A (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © New Phytologist Foundation U.S. Government work - Not all authors are U.S. Government employees.